Prevention of knee and anterior cruciate ligament injuries through the use of neuromuscular and proprioceptive training: An evidence-based review - Dargo, L.; Robinson, K. J.; Games, K. E. (Journal of Athletic Training, 2017)
Clinical Question: Is neuromuscular and proprioceptive training effective in preventing knee and anterior cruciate ligament (ACL) injuries?